Connective Action dan Hashtag activism di Twitter/X Case Studi: Pemilihan Presiden 2024 Pendekatan Social Network Analyst - Nugraha, Mohd Yudhistira Septian; Fitria Ayuningtyas; Munadhil Abdul Muqsith (Universitas Medan Area, 2024)
This article discusses the use of hashtags on the social media platform Twitter in the context of the 2024 Presidential and Vice Presidential election. Hashtags function as a flexible communication tool that facilitates the search for large collections of posts. Utilizing the theory of Connective Action, this research explores public participation in the production and distribution of shared ideas on social media collectively without formal organization. This study examines the use of the hashtags #AniesMuhaimin2024, #GanjarMahfud2024, and #PrabowoGibran2024 by supporters of the 2024 presidential and vice-presidential candidates. The aim is to identify the formation of connective action and observe the interaction patterns among supporters through related hashtags. The method used is Social Network Analysis (SNA), with data collection using scraping and the tweet harvest library via Google Collaboratory. The communication network visualization is carried out using Gephi software. The analysis results show that the hashtag #AniesMuhaimin2024 has 2136 nodes, 2437 edges, an Average Degree of 1.141, and an Average Path Length of 3.268, indicating interconnectedness in information dissemination. The hashtag #GanjarMahfud2024 has 1714 nodes, 2199 edges, an Average Degree of 1.123, and an Average Path Length of 3.355, indicating a fairly good level of interconnectedness among supporters. Meanwhile, the hashtag #PrabowoGibran2024 has 891 nodes, 977 edges, an Average Degree of 1.113, and an Average Path Length of 3.294, showing interconnectedness among supporters This research concludes that through the use of hashtags, supporters of each candidate can express their support and connect on relevant topics on Twitter. The presidential and Vice Presidential Candidates pairs in 2024, and connect on topics through the use of hashtags.